Assessment of immunological response to digital dermatitis pathogen derived antigens following infection, recovery, and reinfection - Coatney, John W.; Krull, Adam C.; Gorden, Patrick J.; Shearer, Jan; Humphrey, Samuel; Olsen, Steven; Plummer, Paul J.; Wilson-Welder, Jennifer H. (Frontiers in Veterinary Science, 2024)
The ability to reliably induce bovine digital dermatitis (DD) in naive calves provides unique opportunities to evaluate immune responses of the calves to infection after disease induction, during healing, and after subsequent re-infection. Dairy calves infected in a previous induction trial were held until lesions resolved and were then re-infected in parallel with naïve calves. Humoral and cell-mediated responses were assessed via serum antibody titer and lymphocyte proliferation analysis with responses of previously infected calves compared with responses of the newly infected calves and naïve calves. In addition, feet of calves in both treatment groups were photographed and scored by a single blinded observer using a previously described induced lesion scoring system. All naïve calves developed lesions after initial infection whereas only 5 of 8 calves developed lesions consistent with DD after a second experimental infection. In the naïve group, lesions commensurate with DD occurred in 15 of 26 experimentally infected feet with 6 feet not included in the analysis due to bandage failure. In comparison, calves in the second infection group developed lesions in 10 of 25 infected feet. Humoral responses or cellular proliferative responses did not differ between the two treatment groups or between calves which developed or did not develop lesions after experimental infection. Our results indicate that resolution of lesions after DD infection, immunity only provides partial protection against reinfection. Further studies are needed to determine immune mechanisms that provide the observed partial protection against reinfection with DD.